2007
DOI: 10.1016/j.neuron.2007.06.029
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Yin Yang 1 Is Essential for Oligodendrocyte Progenitor Differentiation

Abstract: The progression of progenitors to oligodendrocytes requires proliferative arrest and the activation of a transcriptional program of differentiation. While regulation of cell cycle exit has been extensively characterized, the molecular mechanisms responsible for the initiation of differentiation remain ill-defined. Here, we identify the transcription factor Yin Yang 1 (YY1) as a critical regulator of oligodendrocyte progenitor differentiation. Conditional ablation of yy1 in the oligodendrocyte lineage in vivo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
263
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(279 citation statements)
references
References 88 publications
(79 reference statements)
11
263
2
Order By: Relevance
“…It is possible that changes to the size and structure of the nucleus induce transcriptional activity necessary for oligodendrocyte differentiation. Perhaps an increase in cell density affects transcription factors known to regulate differentiation, such as Nkx2.2, Sox10, Olig2, and the recently identified Yin Yang 1 (14)(15)(16)(17). Understanding the relationship between intrinsic and extrinsic factors could help identify environmental conditions that will promote oligodendrocyte differentiation in the presence of chronic demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that changes to the size and structure of the nucleus induce transcriptional activity necessary for oligodendrocyte differentiation. Perhaps an increase in cell density affects transcription factors known to regulate differentiation, such as Nkx2.2, Sox10, Olig2, and the recently identified Yin Yang 1 (14)(15)(16)(17). Understanding the relationship between intrinsic and extrinsic factors could help identify environmental conditions that will promote oligodendrocyte differentiation in the presence of chronic demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…The initial specification of the oligodendrocyte lineage is dependent on olig2 and this lineage is absent from olig2-null mice [17] . olig2 induces transcription factors that are required for the generation of mature, postmitotic oligodendrocytes, notably olig1, Sox-10, Nkx2.2, Nkx6.2, Ying Yang 1, and ZFP488 [18][19][20][21][22][23] . in counterbalance, transcription [24][25][26] .…”
Section: Intrinsic Signalsmentioning
confidence: 99%
“…S6B). In addition, promoter region reporter assays revealed that two important oligodendrocyte-associated transcription factors for OPCs differentiation to OLs, YY1 and Nkx2.2 (17,18), display positive effects on the expression of 2700046G09Rik (Fig. 5G).…”
Section: Overexpression Of Mir-23a Leads To Enhanced Myelination In Thementioning
confidence: 99%